2010
DOI: 10.1007/s10517-010-0860-0
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Inhibits Contraction of Smooth Muscle Cells in Lymphatic Vessels

Abstract: Heparin in concentrations of 10-50 U/ml produced a decrease in the amplitude and frequency of phasic contractions of smooth muscle cells of bovine mesenteric lymphatic vessels. Vascular wall tension was reduced under these conditions. The endothelium-dependent effect of heparin is realized via an increase in the production of nitric oxide by endothelial cells and, to a lesser degree, via the stimulation of prostacyclin synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…It was also shown that heparin modulated lymph vessel contractions by stimulating NO production by endotheliocytes [1]. In the present study, addition of L-NAME (NO synthase blocker) to bathing solution 20 min before heparin led to a signifi cant attenuation of the relaxing effects of heparin.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…It was also shown that heparin modulated lymph vessel contractions by stimulating NO production by endotheliocytes [1]. In the present study, addition of L-NAME (NO synthase blocker) to bathing solution 20 min before heparin led to a signifi cant attenuation of the relaxing effects of heparin.…”
Section: Resultssupporting
confidence: 57%
“…The NO in smooth muscle cell cytoplasm of LN capsules, similarly as in the myocytes of blood and lymph vessels, activates soluble guanylate cyclase, which leads to an increase in cGMP concentration with subsequent activation of ATP + K + channels and development of SM relaxation responses [1,5,10]. Preliminary addition of methylene blue (n=8) or glibenclamide (n=11) into bathing solution attenuated the relaxing effects of heparin (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, there may be differences in the extent of lymphangion regional variation between mesenteric lymphatics and larger collecting ducts (e.g., thoracic duct) and even more variation between species. For example, Lobov 27 described a more rigid valvular portion in bovine mesenteric lymphatic vessels. We believe that his results are attributable to both the larger vessel diameter and the greater smooth muscle component of those lymphatic vessels.…”
Section: Discussionmentioning
confidence: 99%
“…In particular it has been shown that histamine is a potent dosedependent modulator of lymphatic contractility (16 -18, 33, 49, 54 -57, 59, 70, 71). Other mast cell-derived mediators like heparin (40,55), serotonin (15,33,54,70), leukotrienes B4 and C4 (17,33), and thromboxane A 2 (59,65) are also shown to have physiological effects on lymphatic contractility. However, until now, in only one study (59) the activation and degranulation of mast cells has been directly linked to subsequent changes in lymphatic contractility mediated by histamine.…”
mentioning
confidence: 99%